Application of Microservice Platform Design in Rail Transit Intelligent Operation and Maintenance Products - HE Jiabei; HUANG Cheng; WANG Duo (Kongzhi Yu Xinxi Jishu)
In order to solve the problems of repeated construction of chimney development and low scalability of single node service under the traditional mode, this paper introduces advanced technologies such as microservice and docker in the internet industry to build a microservice platform suitable for the field of rail transit intelligent operation and maintenance, and takes a set of FORESEE rail transit intelligent operation and maintenance products as an example, the overall architecture design of microservice platform and the design of microservice cluster are introduced in detail. The microservice platform adopts an efficient engineering development mode and aims at platform reuse, mass production and distribution. Through the actual application of the microservice platform, it can be seen that its application can reduce the average human investment by 70%, reduce the cost and threshold of deployment and operation and maintenance, and achieve the purpose of cost reduction and efficiency improvement.